Strategies To Implement Energy Savings In Hospital Buildings: Perception Of Designers - Maulud, Mohammad Hafiz; Omar, Roshartini (Research in Management of Technology and Business, 2023)
Due to the fact that they are open around the clock, hospitals are one of the buildings that consume the most energy. The Heating, Ventilation, and Air Conditioning (HVAC) systems at hospitals are responsible for the majority of the electrical energy that is consumed there. The application of designs for reducing a building’s energy consumption is not where it should be in Malaysia’s buildings. Through the incorporation of energy saving designs into hospital buildings, hospitals are able to provide healthcare facilities to humanity while simultaneously lowering the amount of energy that they use. The vast majority of a human’s life will be spent inside of structures of some kind. The primary purpose of this research is to investigate the degree to which designers are able to implement energy-saving measures in hospital buildings, to investigate the difficulties that designers face when trying to implement energy-saving measures in hospitals, and to investigate the strategies that designers can employ in order to improve their ability to implement energy-saving measures in hospitals. Because of this, a study was carried out to determine, from the perspective of hospital building designers, the methods that can be used to reduce energy consumption in healthcare facilities. This study concentrates on the hospitals located in Johor Bahru To collect data and information for this study, the researcher uses qualitative methods of data collection. The primary data is gathered through an interview question in a form of a Google Form. Books, articles, journals, and thesis papers that are in some way of collecting secondary data. As a result of data collection and analysis, the findings in this study revealed that many hospitals have started implementing energy savings in their buildings. The challenges that is most faced by designers are the budget of the client. Finally, designing a bigger window to introduce more natural lights and design a more efficient layout of the hospital is the top two strategies needed to be made by designers to ensure the implementation energy savings in hospitals.